A case of erenumab, a new migraine medication, and delayed wound and bone healing after foot and ankle surgery - Timothy Cheung, DPM, PhD, CPT; Zachary Korwek, DPM; Arij Rashid, DPM, AACFAS; Rumzah Paracha, MD; Ashley Bruno, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases)
Patient selection and optimization are crucial components of successful surgery outcomes. Erenumab is a Calcitonin Gene-Related Peptide (CGRP) antagonist that was recently approved by the FDA for the treatment of migraines. CGRP is a neuropeptide implicated in migraines, but is also essential in osteotomy healing. This case reports a pathologic fracture suspected secondary to an elusive side effect of a migraine medication with subsequent delayed wound and osteotomy healing in a healthy patient that underwent an index midfoot arthrodesis and revision. The delayed wound healing lasted approximately 9 months, but once erenumab was identified as the cause of nonunion and delayed wound healing, the medication was stopped and the wound healed 2 weeks later at the next appointment. After withholding of erenumab, there were no significant changes to the foot from serial radiographs. The joint surfaces were stable with manual manipulation and the patient did not have pain with direct palpation to the surgical sites, suggesting fibrous union. This case substantiates the need for considering erenumab, a specific migraine medication, in the preoperative planning and optimization in elective foot and ankle surgery.Level of evidence: IV, case study